Study of Influential Factors That Affect LGBTQ’s Travel Destination Choice Decision - Wongsunopparat, Sumas; Hu, Xiong (Business and Economic Research, 2023)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">LGBTQ tourism is a very promising market with annual worldwide economic impact at more than 140 billion USD. The global LGBT tourism market is expected to reach US$ 568.5 Billion by 2030. The LGBT tourism market is important both economically and socially. LGBT travelers are often high-spending and frequent travelers, and their tourism dollars can have a significant impact on local economies. With the introduction of the 'pink dollar,' organizations hope to tap into members of the LGBTQ+ community who are willing to spend big. The 'pink dollar' refers to money spent by members of the LGBTQ community in the United States. It has boosted the US economy by billions of dollars. Additionally, by creating welcoming and inclusive travel experiences for LGBT individuals, the tourism industry can help promote greater acceptance and understanding of LGBT people around the world. LGBT travelers have unique needs and preferences when it comes to travel, and the tourism industry has responded with a range of products and services designed to meet these needs. These may include LGBT-friendly accommodation, events, and tours, as well as marketing and outreach efforts that specifically target the LGBT community. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The purpose of this research is to study factors influencing LGBTQ’s Travel Destination Choice Decision. These factors include nine independent variables: Recommendations (RE), Popularity (PO), Destination Information (DI), Special Offers (SO), Nearness (NN), Amenities/Facilities (AF), Safety & Security (SS), Destination Features (DF), Strategic Fit (SF) and one dependent variable: Travel Behavior (TB). 400 sample were collected using electronic questionnaire through social media. We used Structural Equation Models (SEM) for data analysis. The result shows that since the RMSEA, which is an absolute fit index that assesses how far our hypothesized model is from a perfect model, for this model is .04 (<.05) which strongly indicates a “close fit” and the Goodness of Fit Index (GFI) value is .904 (>.90), the model seems to fit well according to the descriptive measures of fit. More importantly, Recommendations (RE) and Safety & Security (SS) are significantly defined as significant influential factors that affect LGBTQ’s travel destination choice decision due to their p-values are equal and less than .05. That means LGBTQ choose their travel destination if it’s strongly recommended by friends & family, online & social media, and customer positive review & sharing tips. Moreover LGBTQ prefer the destinations that offer personal safety and safe accommodation and destinations that they won’t be taken advantage of financially i.e. safe and sound destinations without being scammed.